ULTRASTRUCTURAL STUDIES ON THE PERMEABILITY OF THE MESOTHELIUM TO HORSERADISH PEROXIDASE - Cotran, Ramzi S. (The Rockefeller University Press, 1968)
Peritoneal mesothelium was exposed for 2–60 min to solutions of horseradish peroxidase by incubation in vitro, or after intraperitoneal injection in vivo. Peroxidase was localized, with the electron microscope in the intercellular clefts of the mesothelium, often along their entire lengths, in vesicles adjoining or contiguous with the clefts, and along the peritoneal and basal surfaces of the cell, and also in intracytoplasmic vacuoles. The intercellular junctions of peroxidase-treated mesothelium did not differ from those of controls: open and closed junctions were present in both groups. Intercellular localization was also obtained when the mesothelium was exposed to peroxidase during or after fixation. Although intracellular absorption of peroxidase and its incorporation into larger vacuoles were observed, there was no clearcut evidence of vesicular transport across the mesothelium in these experiments. These findings are consistent with physiologic data which postulate that mesothelial transport can be accounted for, at least in part, by passive diffusion through a system of pores, and they suggest that these pores are located in the intercellular clefts.